Ferroelectric and dielectric properties in Ba5SmFe1·5Nb8·5O30 tungsten bronze ceramics. (October 2013) - Zhu, X L; Bai, Y; Liu, X Q; Chen, X M
Abstract: The dielectric and relaxor properties of Ba5 SmFe1·5 Nb8·5 O30 tungsten bronze ceramics were investigated together with the crystal structure. Tetragonal filled tungsten bronze structure was determined in space group P 4 bm with lattice parameters of a = b = 12·527(6) Å, c = 3·955(2) Å. Three dielectric relaxations were observed in the temperature range from 128 to 623 K. A temperature stable dielectric constant plateau (∼2·5×10 3 ) was observed between the middle and high temperature relaxations. The low temperature dielectric relaxation (∼250 K) illustrated a typical relaxor ferroelectric behaviour. The middle temperature dielectric relaxation (dispersing from ∼150 to 450 K) and the high temperature dielectric relaxation (>500 K) were Debye type thermal active processes. The middle temperature relaxation had an active energy with a magnitude of 10 −1 eV, and a relaxation frequency of ∼10 8 Hz was attributed to the inhomogeneous structure. The high temperature relaxation with an active energy ∼1·4 eV and a relaxation frequency ∼10 16 Hz was attributed to the electrode polarisation. Introduction of Fe ions generates large and temperature stable dielectric constant between the middle temperature and high temperature relaxations, disturbs the polarisation ordering and depresses the ferroelectric relaxation temperature.